2016
DOI: 10.1073/pnas.1518931113
|View full text |Cite
|
Sign up to set email alerts
|

Attention promotes episodic encoding by stabilizing hippocampal representations

Abstract: Attention influences what is later remembered, but little is known about how this occurs in the brain. We hypothesized that behavioral goals modulate the attentional state of the hippocampus to prioritize goal-relevant aspects of experience for encoding. Participants viewed rooms with paintings, attending to room layouts or painting styles on different trials during high-resolution functional MRI. We identified template activity patterns in each hippocampal subfield that corresponded to the attentional state i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
157
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(183 citation statements)
references
References 61 publications
(89 reference statements)
16
157
2
Order By: Relevance
“…However, our results on character-specific representations may not appear entirely consistent with studies which suggest that the hippocampus is not sensitive to individual items (e.g., Copara et al, 2014;Hsieh et al, 2014; but see Schlichting et al, 2015;Aly and Turk-Browne, 2016). What could account for such differences?…”
Section: Discussioncontrasting
confidence: 83%
“…However, our results on character-specific representations may not appear entirely consistent with studies which suggest that the hippocampus is not sensitive to individual items (e.g., Copara et al, 2014;Hsieh et al, 2014; but see Schlichting et al, 2015;Aly and Turk-Browne, 2016). What could account for such differences?…”
Section: Discussioncontrasting
confidence: 83%
“…Two recent human fMRI studies (16,17) have demonstrated that HPC representations, as evidenced in voxel activation patterns, are distinct for different task states. In these studies, searching through room images for a particular style of wall art evoked distinct HPC patterns relative to searching the same room images for a particular room layout.…”
Section: Discussionmentioning
confidence: 99%
“…First, HPC rapidly learns (13), an ability important for updating conceptual representations in the face of changing goals. Second, HPC has also been shown to activate representations that are goal relevant (14)(15)(16)(17)(18)(19). A critical open question is how the same experiences come to be represented differently in neural terms as a function of changing conceptual knowledge.…”
mentioning
confidence: 99%
“…Moreover, single bouts of coordinatively demanding physical activity have been found to improve attention in adolescents (Budde et al, 2008), and chronic interventions employing coordinatively demanding physical activity have successfully improved children's attention (Chang et al, 2013; Gallotta et al, 2015). Attention is a key mediator of hippocampal-related declarative memory formation (Aly and Turk-Browne, 2016), probably related to schema-dependent academic learning and performance (van Kesteren et al, 2014). …”
Section: Discussionmentioning
confidence: 99%